THE ROLE OF JAPAN IN THE INDONESIAN ECONOMIC DEVELOPMENT - Nopirin Nopirin (Faculty of Economics and Business, Universitas Gadjah Mada, 1995)
The role of Japan in the development of the Indonesian economy is inevitably getting bigger. Japan is the biggest market for Indonesian exports. As it does in exports, Japan is also the biggest sources of import. From the bilateral sources of debts, it is obvious that Japan is also the biggest sources of loan. In regard of getting the role of Japan, a certain kinds of awareness should be taken by the Japanese Government to lessen the negative feeling of the society that might rise to that which happened in 1974 will never take place again.